Pengaruh infusa daun pepaya terhadap ikan nila yang terinfeksi Aeromonas hydrophila - Dian Puspitasari; Jeki; Intan Zahar (Jurnal Penelitian Pendidikan IPA, 2024)
This study aimed to determine the effectiveness of papaya leaf infusion against the weight gain of Nile tilapia infected with Aeromonas hydrophila and identify the active compounds contained therein.This study used a complete randomized design. The treatment consists of 5 treatments: treatment K (control), treatment A (25 ppt), treatment B (50 ppt), treatment C (75 ppt), and treatment D (100 ppt). This research includes several stages, the first being to infect tilapia with A. hydophila. The second stage is to mix papaya leaf infusion into the feed and observe behaviour, clinical symptoms, weight gain, water quality parameters, and phytochemical analysis. Results showed that treatment A showed the highest value for weight gain. Active compounds in papaya leaf infusion are alkaloids, flavonoids, terpenoids/steroids, glycosides, saponins, and tannins. Papaya leaf infusion increased the weight gain of Nile tilapia infected with A. hydrophila.